QR based management system for plants shopping center - Saja Nasir; Salih Al-Qaraawi; Muayad Sadik Croock (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
It is well known that the development in the life style requires a robust enhancement in the provided services based on technologies. This paper suggests a mobile application under android environment that manages the information and sale systems regarding plants shop. The proposed application uses the Quick Response (QR) codes as identification of an object (plant). The proposed system includes two parts: server and client. The server side contains the most software application, such as database, while the client (mobile) side runs the website based interface between the application and users. QR tag is attached to each plant on the farm to be read by visitor’s mobile camera and sent to the server side using the designed web application. The received QR code is processed by the server and preparing the response with full information of a plant to be sent back to the mobile for user viewing. In addition, the proposed system offers a sale service to the user after performing registration. The proposed system is tested over different case studies and the obtained results show the efficiency of its performance.